2019
DOI: 10.1021/acs.analchem.9b00574
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Modulating Role of Extracellular pH in Permeation and Accumulation of Small Molecules in Subcellular Compartments of Gram-negative Escherichia coli using Nonlinear Spectroscopy

Abstract: Quantitative evaluation of small molecule permeation and accumulation in Gram-negative bacteria is important for drug development against these bacteria. While these measurements are commonly performed at physiological pH, Escherichia coli and many other Enterobacteriaceae infect human gastrointestinal and urinary tracts, where they encounter different pH conditions. To understand how external pH affects permeation and accumulation of small molecules in E. coli cells, we apply second harmonic generation (SHG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(64 citation statements)
references
References 60 publications
(162 reference statements)
4
56
0
Order By: Relevance
“…SHG is a nonlinear optical technique that is sensitive to molecular species at interfaces and has previously been applied to the study of small molecules interacting with both model (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and living cell membranes (21)(22)(23)(24)(25)(26)(27)(28)(29). In SHG, incoming light at a frequency u with sufficient intensity induces a second-order polarization in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…SHG is a nonlinear optical technique that is sensitive to molecular species at interfaces and has previously been applied to the study of small molecules interacting with both model (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and living cell membranes (21)(22)(23)(24)(25)(26)(27)(28)(29). In SHG, incoming light at a frequency u with sufficient intensity induces a second-order polarization in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic mechanism has previously been employed to monitor molecular adsorption and transport across phospholipid membranes in biomimetic model liposomes (12)(13)(14)(15)(16)(17)(18)(19) and living cells. (20)(21)(22)(23)(24)(25)(26)(27)(28) When SHG-active molecules adsorb onto the exterior surface of the membrane, they align with one another due to the similarity of the interaction driving the adsorption process. This oriented ensemble of SHG-active molecules gives rise to a coherent SHS response, the intensity of which scales as the square of the molecular surface density.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, other groups have recently begun adopting this approacht oc haracterize molecular adsorption and membrane transport in living cells, primarily bacteria. [29,30] Prior to this, the patch clamp and av ariety of fluorescence-based techniques were the standard go-to methods for studying molecular transport across membranes. While the patch clamp technique is routinelyu sed to measurem embrane transport of ions, [31] it is not well suited for dealing with neutral molecules or cells with multiple membranes,s uch as bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated an alternative label‐free method for detecting adsorption and transport of small molecules at the membranes of biological cells. Indeed, other groups have recently begun adopting this approach to characterize molecular adsorption and membrane transport in living cells, primarily bacteria . Prior to this, the patch clamp and a variety of fluorescence‐based techniques were the standard go‐to methods for studying molecular transport across membranes.…”
Section: Introductionmentioning
confidence: 99%